Health care professionals' experiences of how an eHealth application can function as a value-creating resource - a qualitative interview study - Catharina Carlqvist; Heidi Hagerman; Markus Fellesson; Mirjam Ekstedt; Amanda Hellström (BMC, 2021)
Abstract Background The number of patients with one or more chronic conditions is increasing globally. One strategy to achieve more sustainable care for these patients is by implementing use of home-based eHealth applications. Such services support patients to take on a more active role as value-creating co-producers of their own care, in collaboration with health care professionals. Health care professionals have a key role in the value creation process, but little is known about value formation within eHealth interactions, especially from their perspective. Therefore, this study aimed to provide a deeper understanding of how an eHealth application can function as a value-creating resource from the perspective of health care professionals. Methods Semi-structured interviews were conducted with thirteen health care professionals (nurses, physicians and first-line managers). Qualitative content analysis was used to analyze the interviews. Results The findings indicate that value formation processes are strongly influenced by the organizational preconditions and by the usability and functionality of technology. The experiences of the health care professionals indicated that value was conceptualized in dimensions of meaningfulness, building of relationships, building safety and feelings of trust. Although these dimensions were mainly expressed in a positive way, such as perceived improvement of medical care, accessibility and continuity, they also had a negative side that caused value destruction. This was primarily due to patient difficulties in using the application or making measurements. Subsequent efforts at value recovery resulted in value creation, but were often time-consuming for the professionals. Conclusions This study contributes by extending conceptualizations of value to the role of health care professionals and by highlighting technology as sometimes facilitating and sometimes hampering value formation processes. The findings indicate that the eHealth application was a value-creating resource, facilitating proactive communication and supporting patients' engagement and control over their self-care. However, for the application to become a more valuable resource in practice and counteract inequity in care, it needs to be further developed to be adapted to the needs and preconditions of patients.